Pengaruh Kualitas Pelayanan Publik dan Citra Kantor Camat Kuta Selatan Terhadap Tingkat Kepuasan Masyarakat - Devi, Ni Kadek Tasya Novita; Suwirmayanti, Ni Luh Gede Pivin (STEKOM PRESS, 2023)
This study aimed to analyze the effect of service quality and the image of the South Kuta District Office on community satisfaction in the South Kuta District area. Sampling techniques in research using techniques purposive sampling involving 100 respondents. Methods of data collection using a questionnaire. Testing the quality of the instrument is done by analyzing the validity and reliability of the instrument. The analysis technique used is multiple regression with the help of the SPSS program. The results showed that 1) partially the quality of service at the South Kuta sub-district office has a significant effect on community satisfaction; 2) partially the image of the South Kuta District Office has a significant effect on community satisfaction; 3) simultaneously the quality of service and the image of the South Kuta District Office have a significant effect on community satisfaction. The simultaneous contribution of service quality variables and the image of the South Kuta District Office to community satisfaction is 94.3%.